Homozygous deletion in MICU1 presenting with fatigue and lethargy in childhood. (April 2016) - Lewis-Smith, David; Kamer, Kimberli J.; Griffin, Helen; Childs, Anne-Marie; Pysden, Karen; Titov, Denis; Duff, Jennifer; Pyle, Angela; Taylor, Robert W.; Yu-Wai-Man, Patrick; Ramesh, Venkateswaran; Horvath, Rita; et al.
Abstract : Objective: To define the mechanism responsible for fatigue, lethargy, and weakness in 2 cousins who had a normal muscle biopsy. Methods: Exome sequencing, long-range PCR, and Sanger sequencing to identify the pathogenic mutation. Functional analysis in the patient fibroblasts included oxygen consumption measurements, extracellular acidification studies, Western blotting, and calcium imaging, followed by overexpression of the wild-type protein. Results: Analysis of the exome sequencing depth revealed a homozygous deletion of exon 1 of MICU1 within a 2, 755-base pair deletion. No MICU1 protein was detected in patient fibroblasts, which had impaired mitochondrial calcium uptake that was rescued through the overexpression of the wild-type allele. Conclusions: MICU1 mutations cause fatigue and lethargy in patients with normal mitochondrial enzyme activities in muscle. The fluctuating clinical course is likely mediated through the mitochondrial calcium uniporter, which is regulated by MICU1.